Ion channel mediated mechanotransduction in immune cells. Issue 6 (December 2021) - Atcha, Hamza; Jairaman, Amit; Evans, Elizabeth L.; Pathak, Medha M.; Cahalan, Michael D.; Liu, Wendy F.
Abstract: The immune system performs critical functions to defend against invading pathogens and maintain tissue homeostasis. Immune cells reside within or are recruited to a host of mechanically active tissues throughout the body and, as a result, are exposed to varying types and degrees of mechanical stimuli. Despite their abundance in such tissues, the role of mechanical stimuli in influencing immune cell function and the molecular mechanisms responsible for mechanics-mediated changes are still poorly understood. The recent emergence of mechanically-gated ion channels, particularly Piezo1, has provided an exciting avenue of research within the fields of mechanobiology and immunology. Numerous studies have identified roles for mechanically-gated ion channels in mechanotransduction within various different cell types, with a few recent studies in immune cells. These initial studies provide strong evidence that mechanically-gated ion channels play pivotal roles in regulating the immune system. In this review, we discuss characteristics of ion channel mediated mechanotransduction, review the current techniques used to quantify and visualize ion channel activity in response to mechanical stimuli, and finally we provide an overview of recent studies examining the role of mechanically-gated ion channels in modulating immune cell function.